The Role Of Sunday School Teachers In The Character Building Of High School Children At GBIS Salatiga - Hery Wibowo; Olis Olis (International Forum of Researchers and Lecturers, 2024)
Character is important in human life. Character building must begin at an early age. The church must also realize this, because the church has an important role in shaping character, especially the character of Christ in children. Through the teaching of Sunday school teachers, the church can take part in the formation of children's character at an early age. The role of a Sunday school teacher is quite large for the character building of Sunday school children. Therefore, Sunday school teachers must know the importance of childhood, the role of Sunday school teachers in the formation of children's character, the process of character formation, influencing factors in character formation and shaping children's character according to the stages of child development. The purpose of this study is to determine the extent to which the role of Sunday school teachers in GBIS Salatiga on the character building of Sunday school children in GBIS Salatiga. This research was conducted using qualitative method and data collection was done through interviews. The results of the research were then reviewed in detail and critically using theoretical studies so that it is known to what extent the role of Sunday school teachers regarding the character building of Sunday school children in GBIS Salatiga.